Congenital true pancreatic cyst: A rare case - Kazez, Ahmet; Akpolat, Nusret; Kocakoç, Ercan; Parmaksiz, Mehmet Ergun; Köseo?ullari, Ayşe Aysel (My University, 2006)
Congenital true pancreatic cysts are very rarely seen in children. We report magnetic resonance imaging features of a case of congenital true pancreatic cyst with a high level of enzymatic activity which, to the best of our knowledge, have not previously been reported. A 4-month-old boy was admitted to our clinic with a history of abdominal swelling for one month. A mobile, smooth, non-tender mass was palpated on the left side of the abdomen during physical examination. Ultrasonography and MR imaging revealed a bilocular cystic mass sized 9.5 × 8 × 6 cm. The spleen was displaced superiorly, whereas the left kidney was displaced posteriorly. Obliteration of the peripancreatic fat planes between the cystic mass and tail of the pancreas was observed. During abdominal surgical exploration, the pancreatic tail was larger than normal, and a pancreatic cyst arising from the tail of the pancreas was observed. Total cystectomy was performed with distai pancreatectomy. Although it is extremely rare in children, congenital true pancreatic cysts should be diagnostically considered in cases involving a cystic mass neighboring the pancreas. MR imaging is not helpful in differential diagnosis of other cysts originating from neighboring organs. Total excision with distal pancreatectomy and splenic preservation are advised for distal pancreatic cysts. © Turkish Society of Radiology 2006.
Keywords: Child; Cyst; Magnetic resonance imaging; Pancreas